Managerial Work in a Practice-Embodying Institution: The Role of Calling, The Virtue of Constancy - Beadle, Ron (2013)
What can be learned from a small scale study of managerial work in a highly marginal and under-researched working community? This article uses the ‘goods–virtues–practices–institutions’ framework to examine the managerial work of owner–directors of traditional circuses. Inspired by MacIntyre’s arguments for the necessity of a narrative understanding of the virtues, interviews explored how British and Irish circus directors accounted for their working lives. A purposive sample was used to select subjects who had owned and managed traditional touring circuses for at least 15 years, a period in which the economic and reputational fortunes of traditional circuses have suffered badly. This sample enabled the research to examine the self-understanding of people who had, at least on the face of it, exhibited the virtue of constancy. The research contributes to our understanding of the role of the virtues in organizations by presenting evidence of an intimate relationship between the virtue of constancy and a ‘calling’ work orientation. This enhances our understanding of the virtues that are required if management is exercised as a domain-related practice.
Keywords: Circus; Constancy; Calling; Virtue; Practice; MacIntyre